Traditional Medicine and Primary Health Care in Sri Lanka: Policy, Perceptions, and Practice - Jones, Margaret; Liyanage, C. (My University, 2018)
Primary Health Care was launched on the international stage by the World Health Organization’s Alma Ata Declaration of 1978. This paper begins by unpicking the concept of primary health care as it evolved after Alma Ata and then explores its implementation in Sri Lanka and the extent to which Ayurveda (a blanket term for the traditional medical systems of Sri Lanka) has been integrated into the government health care system. The substantive part of the paper analyzes the responses of the traditional practitioners who were invited to explore the issues outlined above in a series of interviews. Part historical and part sociological, this discussion of the similarities and the divergences between the approaches of biomedicine and traditional medicine in Sri Lanka from the perspective of the Ayurvedic practitioner exposes the tenuous and disconnected part they play within the biomedical health care system at the practical level.
Keywords: Traditional Medicine and Primary Health Care in Sri Lanka: Policy, Perceptions, and Practice